2021
DOI: 10.3390/microorganisms9071531
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Species as Hosts of Zoonotic Infections: The Case of American Mink (Neovison vison) and Leishmania infantum

Abstract: Leishmania infantum produces an endemic disease in the Mediterranean Basin that affects humans and domestic and wild mammals, which can act as reservoir or minor host. In this study, we analyzed the presence of the parasite in wild American minks, an invasive species in Spain. We screened for L. infantum DNA by PCR using five primer pairs: Two targeting kinetoplast DNA (kDNA), and the rest targeting the ITS1 region, the small subunit of ribosomal RNA (SSU) and a repetitive sequence (Repeat region). The detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…On the one hand, in situ conservation measures are not producing the expected results due to the difficulty of eradicating the exotic American mink in European mink natural areas. The American mink not only competes for the same ecological niche as the European mink but it also poses a threat as a vehicle for infectious pathologies [22] [23] [24]. On the other hand, reproductive management and reproductive methodologies in breeding centers have limitations in obtaining sufficient healthy litters for release into natural habitats [25] [11] [26] and in ensuring appropriate genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in situ conservation measures are not producing the expected results due to the difficulty of eradicating the exotic American mink in European mink natural areas. The American mink not only competes for the same ecological niche as the European mink but it also poses a threat as a vehicle for infectious pathologies [22] [23] [24]. On the other hand, reproductive management and reproductive methodologies in breeding centers have limitations in obtaining sufficient healthy litters for release into natural habitats [25] [11] [26] and in ensuring appropriate genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in situ conservation measures are not producing the expected results due to the difficulty of eradicating the exotic American mink in natural European mink habitats. The American mink not only competes for the same ecological niche as the European mink, but it also poses a threat as a vehicle for infectious pathologies [ 22 , 23 , 24 ]. On the other hand, reproductive management and reproductive methodologies in breeding centers have limitations in obtaining sufficient healthy litters for release into natural habitats [ 11 , 25 , 26 ] and in ensuring appropriate genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides vectorial transmission, vertical transmission and transmission by blood transfusion have been described as well, and recently even in utero transmission were also reported [14]. The domestic dog is the primary reservoir of L. infantum, although other mammalian reservoirs also exist [1,[15][16][17][18]. It has been suggested that cats, rabbits, and ferrets may act not only as accidental hosts, but also as reservoirs [2,[19][20][21][22].…”
Section: Canine Leishmaniosis and Associated Immune Responses 1canine Leishmaniosismentioning
confidence: 98%